Improvement of Vocational Education Curriculum Implementation through Instructional Materials Production and Utilization in Upper Basic Education in Nigeria - Owoh, Titus M. (Asian Journal of Education and Training, 2016)
This article describes the development of curriculum as it relates to vocational education in Nigeria Upper Basic Education Curriculum. The definition of Curriculum development was highlighted to reflect contemporary concepts of curriculum integration. Curriculum development was stressed to include the rudiments necessary in its stages of development. Instructional materials production and utilization in broad terms of audio-visual aids were also treated. The work however drew up the role and relevant position of evaluation in curriculum development. The paper concluded with the need to have the development, production and utilization of instructional materials as a communication channel in the teaching-learning processes of vocational education.